STUDENTS’ BELIEFS ABOUT TEACHING AND THE TEACHING PROFESSION IN THE POST-PANDEMIC ERA - Wawan Setiawan; Ade Surista; Yeni Noryatin (IKIP Siliwangi, 2024)
Beliefs play an important role in teaching and learning because they can impact on teaching behaviors and direct teachers’ decision making about how they will teach in the classroom. Therefore, the researcher attempted to deeply explore students’ beliefs about the teaching and the teaching profession which were classified into four aspects: beliefs about teaching methodology, teachers’ roles, teachers’ challenges, and the teaching profession. The participants were the students who majored in English Literature and they mostly had little teaching experience. The context of exploring the beliefs was in the post-pandemic recovery or when the integration of technology has become the new face of teaching and learning. Through the open questionnaire, it was found that, in the post pandemic era, the teaching methodology should involve offline, online, and blended learning. Second, the roles of teachers were more likely to be facilitators and motivators. Third, the major challenge was in the use of technology itslef, and the teaching professions could be a potential and promosing career and a profession which contested plenty of obstacles.